2011
DOI: 10.1186/1748-717x-6-110
|View full text |Cite
|
Sign up to set email alerts
|

Technology assessment of automated atlas based segmentation in prostate bed contouring

Abstract: BackgroundProstate bed (PB) contouring is time consuming and associated with inter-observer variability. We evaluated an automated atlas-based segmentation (AABS) engine in its potential to reduce contouring time and inter-observer variability.MethodsAn atlas builder (AB) manually contoured the prostate bed, rectum, left femoral head (LFH), right femoral head (RFH), bladder, and penile bulb of 75 post-prostatectomy cases to create an atlas according to the recent RTOG guidelines. 5 other Radiation Oncologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 20 publications
(27 reference statements)
6
48
0
Order By: Relevance
“…These data are in broad agreement with other studies in this area. 5,16,17 The statistical analysis of the various agreement metrics used in this study does not indicate any significant change in the interobserver agreement with and without the use of ABAS apart from the prostate. For this structure, interobserver agreement was significantly improved on three metrics (DSC, logit DSC and MDC) with the use of ABAS using paired Student's t-test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are in broad agreement with other studies in this area. 5,16,17 The statistical analysis of the various agreement metrics used in this study does not indicate any significant change in the interobserver agreement with and without the use of ABAS apart from the prostate. For this structure, interobserver agreement was significantly improved on three metrics (DSC, logit DSC and MDC) with the use of ABAS using paired Student's t-test.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5,16 Two of these 4,16 address the male pelvis. Lin et al 4 gives the timings for individual structures (femurs, prostate, bladder and rectum) and found broadly similar time savings-the rectum was the structure that showed the least time saving in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Five pelvic CT simulation datasets (512 x 512 pixels, 3mm slice thickness, 120 kVp) of five different prostate bed patients were each contoured by an expert panel of five radiation oncologists [1]. The six structures specifically delineated were prostate bed, rectum, bladder, penile bulb, and left and right femoral heads.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that AABS decreases inter-and intra-observer variability as well as contouring time in multiple cancer types [1,[3][4][5]. Yet, some research suggests the need for further improvement of AABS approaches, as illustrated by Hwee, et al where they found that only 12% of their auto-contoured images were considered clinically acceptable by blinded human observers [1]. Previous studies have not characterized, in particular, any differences between single best matching (SBM) and multiple best matching (MBM) approaches, or differences between contours when the number of best matches is varied when using MBM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation